Obese fathers lead to an altered metabolism and obesity in their children in adulthood: review of experimental and human studies - Fernanda Ornellas; Priscila V. Carapeto; Carlos A. Mandarim-; Marcia B. Aguila
Abstract Objective: To discuss the recent literature on paternal obesity, focusing on the possible mechanisms of transmission of the phenotypes from the father to the children. Sources: A non-systematic review in the PubMed database found few publications in which paternal obesity was implicated in the adverse transmission of characteristics to offspring. Specific articles on epigenetics were also evaluated. As the subject is recent and still controversial, all articles were considered regardless of year of publication. Summary of findings: Studies in humans and animals have established that paternal obesity impairs their hormones, metabolism, and sperm function, which can be transmitted to their offspring. In humans, paternal obesity results in insulin resistance/type 2 diabetes and increased levels of cortisol in umbilical cord blood, which increases the risk factors for cardiovascular disease. Notably, there is an association between body fat in parents and the prevalence of obesity in their daughters. In animals, paternal obesity led to offspring alterations on glucose-insulin homeostasis, hepatic lipogenesis, hypothalamus/feeding behavior, kidney of the offspring; it also impairs the reproductive potential of male offspring with sperm oxidative stress and mitochondrial dysfunction. An explanation for these observations (human and animal) is epigenetics, considered the primary tool for the transmission of phenotypes from the father to offspring, such as DNA methylation, histone modifications, and non-coding RNA. Conclusions: Paternal obesity can induce programmed phenotypes in offspring through epigenetics. Therefore, it can be considered a public health problem, affecting the children's future life.